(untitled) (Sains Humanika, 2016)
Dialogue of civilizations is not a new term in the world of human civilization, but its application in human life begins simultaneously with human existence on this earth. It becomes one of the medium to apply the values of understanding and positive interaction between two way communications, sharing perspectives for solving problems in various aspects, tolerance, agreed cooperation, exchange opinions and ideas. As a result, it is able to bring to the circumstances where all parties can benefit or be identified as a win win situation. Besides, the Islamic education is the process of training and educating and molding the character and attitude of the human person. Aiming to foster the perfect personality in many aspects of life in physical, spiritual, mental, even moral social. It needs to be developed based on the values of Islamic and there needs to be alignment between the curriculums with the teachings of Islam itself. The result, then formed a curriculum that corresponds to human nature, corresponding to each age ratings and demands to give birth during the development of a brilliant public institutions. Thus, education and community issues are is implemented effectively, it can act as an agent to maintain and spread the culture according to the progress and development currency. In the context of public high school in teaching institutions the two elements that are very tightly linked and can’t be separated and have the goal of the thorough and parallel to the global situation. If it as a reflection of Malaysian society, instead of them as heir to the country leaders and boosters advanced society. How would the situation prevailing polarization of the conflict and the silent various ethnic, tenuous relationship between religion and nation in the students who should be expected. One approach to dealing with conflict and polarization of people in the students, the Ministry of Higher Education, Malaysia has required students Public University (UA) and Private University (US) took the subject of Islamic Civilization and Asian Civilization, the State and the relationship ethnicity as a preparation towards society mutual respect between each other through the medium of education and dialogue between civilizations. One study analyzed the students’ opinion about the teaching and learning of TITAS has been implemented in UTM. In addition, analyzing the results of the assessment based on the four elements TITAS, the group assignment (20%), presentation (10%), tests or quizzes (20%) and e-learning or generic skills (10%). The results are then analyzed using Statistical Package for Social Science (SPSS) version 20.0 for Windows. The results and findings have clarified the mean (average) which is in the very high or very positive (> 4.00) in the analysis of teaching and learning styles findings and analysis of the findings of the assessment TITAS four elements TITAS. In conclusion, the elements of civilization that has been incorporated into every element in the implementation of the subject TITAS plays a very important role in fostering a tolerant attitude among the races in Malaysia.